2000
DOI: 10.1128/jcm.38.11.3926-3931.2000
|View full text |Cite
|
Sign up to set email alerts
|

Community Acquisition of Gentamicin-Sensitive Methicillin-Resistant Staphylococcus aureus in Southeast Queensland, Australia

Abstract: Community-acquired methicillin-resistant Staphylococcus aureus (MRSA) susceptible to gentamicin has been reported in a number of countries in the 1990s. To study the acquisition of gentamicin-sensitive MRSA (GS-MRSA) in southeast Queensland and the relatedness of GS-MRSA to other strains of MRSA, 35 cases of infection due to GS-MRSA from October 1997 through September 1998 were examined retrospectively to determine the mode of acquisition and risk factors for MRSA acquisition. Thirty-one isolates from the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…48 The emergence of CA-MRSA infections in the eastern cities of Australia occurred in the late 1990s. 49,50 Phage typing of isolates from south-east Queensland suggested that the isolates were related to the WSPP strains seen previously in New Zealand. 50 Skin and soft tissue infections were the main types of infection associated with these strains.…”
Section: Emergence Of Infections Caused By Community-acquired Methicimentioning
confidence: 61%
See 1 more Smart Citation
“…48 The emergence of CA-MRSA infections in the eastern cities of Australia occurred in the late 1990s. 49,50 Phage typing of isolates from south-east Queensland suggested that the isolates were related to the WSPP strains seen previously in New Zealand. 50 Skin and soft tissue infections were the main types of infection associated with these strains.…”
Section: Emergence Of Infections Caused By Community-acquired Methicimentioning
confidence: 61%
“…49,50 Phage typing of isolates from south-east Queensland suggested that the isolates were related to the WSPP strains seen previously in New Zealand. 50 Skin and soft tissue infections were the main types of infection associated with these strains. 49 In common with the New Internal Medicine Journal 2005; 35: S97-S105 Dicloxacillin/flucloxacillin 1-2 g q6h IV 2-3 weeks Patients hypersensitive to penicillin: Cephalothin † or cephazolin † 2 g q6h IV or q8h IM Clindamycin 300 mg -600 mg q6h IV Co-trimoxazole (TMP-SMX) 960 mg q12h IV † Note: between 3% and 8% of patients who are hypersensitive to penicillins will exhibit cross-reactivity with cephalosporins (see review on antibiotics in this issue).…”
Section: Emergence Of Infections Caused By Community-acquired Methicimentioning
confidence: 61%
“…A later study from Queensland of gentamicinsusceptible MRSA showed that 23 of 35 patients had community-acquired infections, and 16 of these 23 patients lacked risk factors associated with nosocomial MRSA acquisition. 39 The strains were non-multiresistant, most were fully susceptible to non-β-lactams and closely related to New Zealand WSPP strains, and most patients were Polynesians. Subsequent work from New South Wales showed that WSPP strains were usually associated with skin and soft tissue infections, but that the infections were much more severe than infections with methicillin-susceptible S. aureus (MSSA) or multiresistant MRSA strains and the majority of patients required hospital admission and surgery.…”
Section: History Of Community Mrsamentioning
confidence: 95%
“…35 The epidemic was most intense in the Auckland area, and the organisms spread widely, including to Australia. 11,14,20,39 In Australia, they are also known as the South-western Pacific 39 or Oceania strain. 40 Multiple case reports and two small series 3,41 were reported from the USA during this period.…”
Section: History Of Community Mrsamentioning
confidence: 99%
See 1 more Smart Citation